PENGARUH MODEL INQUIRI BERBANTUAN ALAT MUSIK PIANIKA TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN SENI MUSIK KELAS IV UPT SPF SDN BAWAKARAENG 1 KOTA MAKASSAR - Ulfani; Hikmawati Usman; Nurhaedah; Sultan Sahrir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Music arts learning for grade IV at UPT SPF SDN Bawakaraeng 1 Makassar City still faces the challenge of low student learning outcomes due to difficulties in understanding the concept of pitch, rhythm, and pianica playing techniques, so an innovative pianica-assisted inquiry model is needed to improve psychomotor skills. This study aims to describe the application of the pianica-assisted inquiry model in music arts learning, analyze student learning outcomes, and test its effect on improving psychomotor learning outcomes for grade IV students. The research method used a quantitative approach with a quasi-experimental pretest-posttest control group design, involving 27 fourth grade students divided into experimental groups (14 students) and control groups (13 students), data were collected through observation and psychomotor tests, and analyzed with descriptive and inferential statistics (Shapiro-Wilk normality test, Levene's homogeneity, independent and paired t-test) using SPSS version 25. The results showed that the application of the pianica-assisted Inquiry model in the experimental group reached a very good category (average 86-100%) at the final meeting, while the control group remained low; the pretest learning outcomes of both groups were low (average 19.62-21.00, incapable category), but the experimental posttest increased significantly (average 41.64, 71.4% very capable) compared to the control (average 31.69, 61.5% capable). The hypothesis test confirmed a significant effect (Sig. 0.000 < 0.05; t-count -10.691) with a greater mean difference in the experiment (-20.643 vs -12.077). The conclusion states that the pianica-assisted Inquiry model is effective in improving students' musical arts learning outcomes.